2021
DOI: 10.1097/mpg.0000000000003293
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Health Status and Quality of Life After Esophageal Atresia Repair

Abstract: Objectives: To longitudinally evaluate self-reported and proxy-reported health status (HS) and quality of life (QoL) of school-aged children born with esophageal atresia (EA). Methods: We obtained Pediatric Quality of Life Inventory (HS) and DUX-25 (QoL) questionnaires from children born with EA between 1999 and 2011 at 8 and/or 12 years old. Children completed self-reports during neuropsychological assessments in a prospective longitudinal follow-up program. Parents filled out proxy-reports at home. Total and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Furthermore, the parental educational level was higher than in the general population. Although this is a common finding in the EA population [ 12 , 48 ] and in psychometric evaluation in general [ 49 ], it should be taken into account that this could lead to bias. Moreover, the online study set-up and some statistical assumptions differed from earlier EA-QOL© validation studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the parental educational level was higher than in the general population. Although this is a common finding in the EA population [ 12 , 48 ] and in psychometric evaluation in general [ 49 ], it should be taken into account that this could lead to bias. Moreover, the online study set-up and some statistical assumptions differed from earlier EA-QOL© validation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite inconsistent findings, studies indicated that children with EA report lower generic HRQoL than do healthy children [ 9 , 10 , 11 , 12 ]. Condition-specific instruments tend to be more sensitive to the detection and discrimination of clinical morbidities, and more suitable for assessing disease burden [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is relevant in that the DUX-25 focuses on a client’s emotional and cognitive evaluation to measure HRQOL, while the PedsQL uses functioning as an indicator. The main difference between these concepts is that while functioning attempts to measure well-being by defining specific concepts externally and objectively, the subjective emotional and cognitive evaluation indicates how an individual actually experiences limitations in specific areas of his or her life [ 41 ]. In certain clinical groups, the subjective and the more objective view of health can produce different results over time, as we have already substantiated in a study in children after oesophageal atresia repair [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herewith, we confirm previous study results, where young children with OA (< 5 years) are affected by any kind of feeding or swallowing problems in about 55–70% of cases, compared to only about 18–30% of older children with OA [ 2 , 8 , 16 , 31 ]. In a recent study from the Netherlands, self-reported health status in children with OA was also increasing with age [ 32 ]. These changes with age might be due to an accommodation of the swallowing ability and integration of feeding disorders by time [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…VACTERL is a combination of various birth defects, such as vertebral defects, anorectal malformations, cardiac defects, OA, tracheo-oesophageal fistula and renal and limb malformations which can cause physical dysfunction. Self-perceived health status in children with OA and VACTERL is also reported to be worse compared to children with OA only [ 32 ]. VACTERL associated life-long conditions such as neurodevelopmental delay and attention deficit may lead to abnormal eating habits.…”
Section: Discussionmentioning
confidence: 99%